A correlation analysis on the postpartum anxiety disorder and influencing factors in puerperae with gestational diabetes mellitus - Zeng, Xun; Yan, Xiaofen; Yang, Yan; Peng, Zhangqing; Wei, Shiyao; Chen, Jinxia; Wu, Fengchun; Chen, Jiebing; Zhao, Ming; Luo, Chunqi (Frontiers in Endocrinology, 2023)
This study was approved by the Institutional Review Board (IRB) of the he First Affiliated Hospital of Sun Yat-sen University, and all participants provided informed consent to participate.All authors contributed to the study design and data interpretation. F.C. Wu and J.B. Chen were responsible for management and oversight of the study. C.Q. Luo and X. Zeng were responsible for general omnibus data analyses and were keys contributing authors to the manuscript. X.F. Yan and Z.Q. Peng were responsible for all research interviews and clinical chart reviews associated with this study. W.S. Yao and J.X. Chen provided guidance on the design of primary analyses. Y.Yang and M. Zhao assisted with all data collection, analysis, and writing of the manuscript.